Business Analytics for Quality Improvement: A Case Study in Healthcare Systems - Sunil Kanojiya; Mohammad Yasin; Mahzabin Binte Rahman; Saif Ahmad; Mahbub Hasan (International Journal of Medical Science and Public Health Research, 2025)
Globally, the healthcare systems are progressively being strained to provide quality care and at the same time managing the costs, resource limitations and the increasing demands of patients. The conventional methods of quality improvement which depend on post-facto audits and manual performance evaluations have been inefficient in offering real-time actionable information about the quality improvement that is required to be sustained. One relatively new instrument to overcome this issue is business analytics (BA), which can provide data-driven frameworks to monitor and assess and optimize healthcare quality metrics. The paper is a case study, which explores how BA can be applied to the healthcare performance tracking with the attention to how descriptive, predictive, and prescriptive analytics can be used in a systematic way to advance quality outcomes. The methodology will incorporate patient care data, operational indicators and institutional records, and they will be examined using the most popular tools, Power BI and Tableau, to monitor the main performance indicators, such as patient wait times, readmission rates, and the number of clinical errors reduced. The results prove that BA does not only ensure transparency in quality measurements but also allows the prediction of probable interventions taking proactive measures that lead to quantifiable enhancement of various performance measures. The research paper fills the current gap between BA frameworks and quality improvement research, as well as offers a practical implication to healthcare administrators and policymakers. The innovative nature of the study is that it showed the potential of BA tools to transform the quality improvement initiatives, whose reporting is static, to continuous optimization when properly integrated into healthcare operations. The presented case study highlights the need to make BA a part of healthcare systems as a strategic force of sustainable quality improvement and organizational excellence.